Catholics and politics : the dynamic tension between faith and power - Heyer, Kristin E., 1974-; Rozell, Mark J.; Genovese, Michael A. (Religion and politics series (Georgetown University), 2008)
Catholic political identity and engagement defy categorization. The complexities of political realities and the human nature of such institutions as church and government often produce a more fractured reality than the pure unity depicted in doctrine. Yet, in 2003 under the leadership of then-prefect Joseph Cardinal Ratzinger (now Pope Benedict XVI), the Congregation for the Doctrine of the Faith issued a Doctrinal Note on Some Questions Regarding the Participation of Catholics in Political Life. The note explicitly asserts, The Christian faith is an integral unity, and thus it is incoherent t.